Soil-structure interaction effects on seismic behaviour of multistorey structures - Aydemir, Muberra Eser; Ekiz, Ibrahim (TAYLOR & FRANCIS LTD, 2013)
This paper addresses the behaviour of multistorey structures considering soil-structure interaction under earthquake excitation. To this end, samples 1, 3, 6, 9, 12 and 15 storey RC plane frames corresponding to aspect ratios (h/) of 1/3, 1, 2, 3, 4 and 5 are designed based on Turkish Seismic Design Code and analysed in time domain with incremental dynamic analysis. Inelastic displacement ratios and strength reduction factors are investigated for designed sample plane frames for 64 earthquake motions recorded on different site conditions such as rock, stiff soil, soft soil and very soft soil. According to the analysis result, strength reduction factors of sample buildings considering soil-structure interaction are found to be smaller than design strength reduction factors, given the current seismic design codes. This condition leads to an unsafe design and non-conservative design forces. Besides, inelastic displacement ratios of fixed-base and interacting cases are found to be quite different especially for periods shorter than .5s.
Keywords: soil-structure interaction; inelastic displacement ratio; strength reduction factor; incremental dynamic analysis; INELASTIC DISPLACEMENT RATIOS; REDUCTION FACTORS; FOUNDATION; DUCTILITY; DESIGN; DEMAND; FRAMES; Engineering